2020
DOI: 10.3390/ma13173895
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Additive Manufacturing Technologies—A Review to Technical Synthesis in Numerical Study of Selective Laser Melting

Abstract: Additive Manufacturing (AM) processes enable their deployment in broad applications from aerospace to art, design, and architecture. Part quality and performance are the main concerns during AM processes execution that the achievement of adequate characteristics can be guaranteed, considering a wide range of influencing factors, such as process parameters, material, environment, measurement, and operators training. Investigating the effects of not only the influential AM processes variables but also their inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 132 publications
0
20
0
Order By: Relevance
“…With pentamode metamaterial reinforcement, elastic strains occurred not only in the heat pipe walls but also in the reinforcement, as seen in the zoomed-in images in Figure 10 . Because Poisson’s ratio of pentamode metamaterials was negative, strain areas in the reinforcement were larger than that in the heat pipe walls [ 19 , 27 , 28 ]. Therefore, stresses in the heat pipes were accommodated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With pentamode metamaterial reinforcement, elastic strains occurred not only in the heat pipe walls but also in the reinforcement, as seen in the zoomed-in images in Figure 10 . Because Poisson’s ratio of pentamode metamaterials was negative, strain areas in the reinforcement were larger than that in the heat pipe walls [ 19 , 27 , 28 ]. Therefore, stresses in the heat pipes were accommodated.…”
Section: Resultsmentioning
confidence: 99%
“…According to above analysis, it was demonstrated that pentamode metamaterial reinforcement could accommodate thermal stresses in sodium/Inconel 718 heat pipes; hence, this was a solution to the thermal-structure problems of alloys. Other potential applications (using different topological structures and different heat pipes) included: limiting thermal distortions of hot structures [ 28 ], cooling of space reactors, and thermal management of hypersonic vehicles. Recently, heat pipes with pentamode reinforcement were designed for space reactor cooling.…”
Section: Resultsmentioning
confidence: 99%
“…This process enables the fabrication of sophisticated customized products without complicated laboratory manual works, unlike conventional manufacturing methods [3]. Powder bed fusion is a form of a 3D printing technology commonly used for metal 3D printing [4,5]. This technology is also referred to as selective laser sintering (SLS), selective laser melting (SLM), direct metal laser sintering (DMLS), or electron beam melting (EBM) in the literature [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Another technological advantage is the ability to produce parts with an almost final shape, thus reducing production time and costs [ 6 ]. Nevertheless, products obtained by AM still require further development on open issues regarding internal defects due to printing errors and residual and thermal stresses, for instance [ 7 , 8 ]. This quality uncertainty can create parts wastage, increase parts delivery time and prevent AM implementation in industries that require high performance components with quality assurance.…”
Section: Introductionmentioning
confidence: 99%